Treatment for chest pain intercurrence after breast cancer surgery using Godoy’s intermittent skin therapy - Pereira de Godoy, Jose Maria; Pereira de Godoy, Henrique Jose; Dias Guimarães, Tania; Guerreiro Godoy, Maria de Fatima (International Journal of Health Sciences, 2021)
Objective: Chest pain and swelling are routinely reported in women after breast cancer treatment and are often not valued by health professionals. In general, these patients suffer and without many effective solutions. The aim of the present study was to report the results of a novel technique for the treatment of chest pain related to breast cancer treatment. Methods: A clinical trial was conducted involving 25 women with chest pain resulting from the treatment of breast cancer and submitted to treatment for lymphedema at the Godoy School in 2018. Godoy’s intermittent dermal therapy was performed on the participants 2–4 h/day for 2 days until the occurrence of a significant improvement or complete resolution of pain (measured using the visual analog pain scale). Results: All patients reported a significant reduction in pain in the first ½ h of treatment (P < 0.0001, Wilcoxon signed-rank test). Six of the 25 patients (24%) reported the absence of pain after treatment on the 1st day and all (100%) reported the absence of pain at the end of treatment on the 2nd day. Conclusion: Chronic chest pain in patients having been submitted to treatment for breast cancer can be significantly reduced with Godoy’s intermittent skin therapy, achieving standards of normality or near normality within only a few sessions.